2021
DOI: 10.1186/s12957-021-02389-x
|View full text |Cite
|
Sign up to set email alerts
|

LINC01224 promotes colorectal cancer progression through targeting miR-485-5p/MYO6 axis

Abstract: Background Long noncoding RNAs (lncRNAs) are related to colorectal cancer (CRC) development. However, the role and mechanism of lncRNA LINC01224 in CRC development are largely unknown. Methods LINC01224, Yin Yang 1 (YY1), microRNA (miR)-485-5p, and myosins of class VI (MYO6) levels were examined using quantitative reverse transcription polymerase chain reaction and western blotting. Functional analyses were processed through CCK-8, colony formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…There are often complicated relationships when they work. For example, linc01224 targets the miR-485-5p/MYO6 axis to promote CRC progression [ 34 ], circ_0082182 functions as an oncogene in CRC by sponging miR-411 or miR-1205 to activate the Wnt/β-catenin pathway [ 35 ], and the circ0009910/miR-145-5p/PEAK1 axis contributes to the pathogenesis of CRC [ 36 ]. Our miR-495-3P may also be regulated by lncRNA or circRNA, which may become the content of our future research.…”
Section: Discussionmentioning
confidence: 99%
“…There are often complicated relationships when they work. For example, linc01224 targets the miR-485-5p/MYO6 axis to promote CRC progression [ 34 ], circ_0082182 functions as an oncogene in CRC by sponging miR-411 or miR-1205 to activate the Wnt/β-catenin pathway [ 35 ], and the circ0009910/miR-145-5p/PEAK1 axis contributes to the pathogenesis of CRC [ 36 ]. Our miR-495-3P may also be regulated by lncRNA or circRNA, which may become the content of our future research.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the lncRNAs have already been confirmed to be significantly related to patient prognosis. Gu et al (2021 ) found that suppression of LINC01224 inhibited CRC cell proliferation, migration, and invasion while increasing apoptosis via the LINC01224/miR-485-5p axis. Qi et al (2019 ) discovered that an elevated level of lncRNA GABPB1-AS1 could inhibit GABPB1 transcription, resulting in the dysregulation of the gene encoding the peroxiredoxin-5 ( PRDX5 ) peroxidase and the suppression of cellular antioxidant capacity, implying that increased GABPB1-AS1 levels may be linked to improved prognosis in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Without the suppression from miR‐361‐3p, overexpressed YY1 accelerates proliferation and glycolysis of CRC cells and the angiogenesis of human umbilical vein endothelial cells (HUVECs), meanwhile positively stimulating MIR31HG level in turn 38 . The similar positive feedback loops were detected as YY1/LINC00667/miR‐449b‐5p axis 39 and YY1/LINC01224/ miR‐485‐5p/myosins of class VI (MYO6) axis 62 . Cooperating with NF‐κB, YY1 directly binds to the promoter of LINC01578 to enhance its activity.…”
Section: Regulating Functions Of Yy1 In Crcmentioning
confidence: 83%